Integrating Mental Health Education into School Curricula: Impacts on Student Well-being and Academic Performance - Arfa Akram; Awais Ur Rahman; Rubia Batool; Tanveer Alam; Sami Ullah; Sniya Siddique; Sundas Sattar (Dialogue Social Science Review (DSSR), 2024)
This study examined the impact of mental health education on students well-being and academic performance through qualitative research involving 100 participants, including 60 high school students and 40 teachers from five different schools. Data were collected through in-depth interviews and focus group discussions, focusing on the perceived effects of mental health education programs. The findings revealed that mental health education significantly improved students emotional regulation, reduced stress and anxiety, and fostered better peer relationships, which in turn enhanced academic engagement and performance. Teachers observed notable behavioral changes, leading to a more positive classroom environment. This research underscores the importance of integrating mental health education into school curricula to promote emotional resilience and academic success among students.